Machinima: Zwischen Dokumentation, Performanz und Abstraktion. - Wenz, Karin (Code / Kodikas)
The following contribution introduces machinima under the following principles: (1) the specific use of the computer as database/archive, (2) the principle of modularity, (3) the numeric representation and (4) transcoding. These aspects will be analyzed in respect of their concrete and abstract representation. The use of the medium for archiving and documentation can be understood as a concrete usage. The medium's modularity has the effect that several sources can be combined to one new expression form or modified on several levels as e.g. the level of textual representation, the programming code or the interface, which can be understood as a more abstract representation on a scale from concrete to abstract. The most abstract representation is transcoding. Additionally the following questions will be answered: "Who produces machinima?" and "what is the function of the communities producing machinima?"